NILAI-NILAI KEARIFAN LOKAL DALAM TRADISI LISAN WARAG-WARAH DAN RINGGOK-RINGGOK SUKU KOMERING, SUMATERA SELATAN (VALUES OF LOCAL WISDOM IN ORAL TRADITION OF WARAH WARAH AND RINGGOK-RINGGOK OF KOMERING TRIBE, SOUTH SUMATRA) - Kurnianto, Ery Agus (ALAYASASTRA, 2017)
The focus of the problem in this study is the values of local wisdom within two oral traditions of Warag-Warah and Ringgok-Ringgok of Komering Tribe, South Sumatra. This study aimed to identify and to describe elements of local wisdom within those oral traditions. In addition, this study was established as a real effort to explore, to inventorize, and to document the oral traditions of Komering society. A descriptive method was applied in this study. The data were analyzed by applying qualitative approach on ethnographic elements to demonstrate and explain the value of local wisdom within those oral traditions. The theory applied in this study were oral literature and local wisdom. The conclusion from the analysis proved that there was a concept of social relations among individuals, among individuals and society, among social groups, and among individuals and their God. The value of local wisdom that had been identified were: 1) belief in God, 2) deliberation, 3) responsibility and 4) helping each other. The actualization of the value of local wisdom within the oral traditions of Warag-Warah and Ringgok-Ringgok was in form of behaving in ways that help each other, solving problems by means of deliberation and responsibility. Keywords: Oral tradition, warah-warah, ringgok-ringgok, local wisdom values.